"Research Mentors Should Support Students of Color by Taking an Extra Step." Undergraduates' Reasoning about Race and STEM Research Mentorship - Kristin Dee Vierra; Diana R. Beltran; Lindsay Denecker; Rachael D. Robnett (MDPI AG, 2024)
Racial inequities and the adoption of a colorblind approach in education contribute to a situation wherein many academics lack the personal experience and incentive needed to identify and confront racism within society and institutions. This may be particularly the case in fields related to science, technology, engineering, and math (STEM), which tend to have lower levels of diversity compared to other fields. The current study examines undergraduates' perceptions of whether STEM research mentors should consider race when mentoring students from marginalized backgrounds. We employ a mixed-methods approach with the goal of uncovering how undergraduate students perceive and rationalize research mentoring practices. Findings reveal that a strong majority of undergraduate students believe that research mentors should take race into account when mentoring students from marginalized backgrounds. During the qualitative coding process, the research team unearthed seven overarching themes that outline undergraduates' reasoning, both in favor and against STEM research mentors considering race. We conclude by presenting an intervention intended to motivate individuals to redress colorblind ideologies and thus support a culturally sensitive mentoring style.